“Volodymyr Vynnychenko’s Play The Law: The Principle of the Genre and Stylistic Complexity - Viktor I. Humeniuk (Studia Litterarum)
The main character of Volodymyr Vynnychenko’s play entitled The Law, a young woman eager to have a child, programs her life the way she desires and solves a difficult life situation, as if she were acting as her own life’s stage director. The play is a chamber family play of five characters. However, Vynnychenko’s family collisions always have a global dimension. The play expresses concern about a totalitarian mindset that tends to achieve a higher goal without considering objective laws of nature and society. The genre of the chamber play and the tragic monumentality of the plot are peculiarly combined in the work allotting it with a sort of artistic integrity. A psychologically compelling story ultimately turns into an intellectual drama and reaches the verge of tragedy. A unity of generic and stylistic aspects is to emphasize the element of play, the use of the “theatre-in-the-theatre” method while the theatre is presented as a prerogative not only of art but also of life.